AB1328-HPR INCREASED BODY MASS INDEX AFFECTS SPINAL MOBILITY RATHER THAN DISEASE ACTIVITY IN ANKYLOSING SPONDYLITIS. (2nd June 2020) - He, M.; Bao, Y.; Yang, Y.; Liu, S.; Dong, C.; Zhou, W.; Guo, J.; Liu, J.; Chen, Y.; Gu, Z.
Abstract : Background: Studies have reported the association between overweight or obesity and ankylosing spondylitis (AS), but their relation is still unclear in China. Objectives: To explore the prevalence of overweight or obesity and its effect on other indicators and their relationships in Chinese AS patients. Methods: Demographic and clinical variables were collected from 207 AS patients. Patients were categorized to normal BMI group (BMI < 23kg/m 2 ) and overweight group (BMI ≥ 23kg/m 2 ). We used Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Bath Ankylosing Spondylitis Functional Index (BASFI), Bath Ankylosing Spondylitis Metrology Index (BASMI), Health Assessment Questionnaire (HAQ), Ankylosing Spondylitis Quality of Life (ASQoL) and Medical Outcomes Study Short Form 36 (SF-36) to evaluate disease activity, physical function, spinal mobility, functional limitation and health-related quality of life, respectively. Statistical analysis used independent t test, Mann-Whitney U test, Chi-square test and Spearman's rank correlation test. Results: 56.5% (117) AS patients were overweight or obese, among which 80.3% (94) were male. In the overweight group, patients were older, more being married, and have higher BMI, higher waist circumference, higher waist-to-hip ratio, longer disease duration, higher BASMI score, higher white blood cell count (WBC), higher lymphocyte and higher platelet count compared to the non-overweight group ( P ≤ 0.038). However, there was no distinct difference in BASDAI score between the two groups ( P = 0.891). In the correlation analyses, gender and marital status ( P ≤ 0.036) were correlated negatively with BMI; while age, waist circumference, waist-to-hip ratio, WBC, lymphocyte count and red blood cell ( P ≤ 0.036) were correlated positively with BMI. Conclusion: Overweight or obesity is common in Chinese AS patients. Increased BMI affects not disease activity but spinal mobility, which indicates that patients with high BMI are more likely to have limitations in flexion, extension, lateral bending and torsion of spine. References: [1]Bowness P. Hla-B27. Annu Rev Immunol. 2015;33:29-48. [2]de Araújo TA, Mota MC, Crispim CA. Obesity and sleepiness in women with fibromyalgia. Rheumatology International. 2014;35(2):281-7. Acknowledgments: This study was funded by Science and technology Project of Nantong City (Grant/Award Number: MSZ18217), Postgraduate Research & Practice Innovation Program of Jiangsu Province (Grant/Award number: KYCX19_2071 and KYCX18_2410), National Natural Science Foundation of China (Grant/Award number: 81671616 and 81871278), Science and technology Project of Jiangsu Province (Grant/Award number: BE2018671) and Clinical Research Center of Stem Cells, Affiliated Hospital of Nantong University, Nantong (Grant/Award number: HS2018001). Disclosure of Interests: None declared